SLC41A1 is the only magnesium responsive gene significantly overexpressed in placentas of preeclamptic women†. (November 2013) - Kolisek, Martin; Galaviz-Hernández, Carlos; Vázquez-Alaniz, Fernando; Sponder, Gerhard; Javaid, Saba; Kurth, Katharina; Nestler, Axel; Rodríguez-Moran, Martha; Verlohren, Stefan; Guerrero-Romero, Fernando; Aschenbach, Jörg Rudolf; Vormann, Jürgen
<x xml:space="preserve">Abstract</x> Objective: To examine expression profile of magnesium responsive genes (MRGs) in placentas of normoevolutive and preeclamptic women. Methods: The expression profiles of MRGs were determined in placentas of normoevolutive (N = 26) and preeclamptic (N = 25) women by RT-qPCR. Results: Among all tested MRGs (9) only SLC41A1 (encoding for Na+/Mg2+ exchanger) was significantly overexpressed in ∼54.2% of preeclamptic (n = 24) and in ∼9.5% of normoevolutive (n = 21) specimens. On average, SLC41A1 was overexpressed sixfold in the preeclamptic group. Presence of SLC41A1 in placentas was confirmed by Western blot analysis. Conclusion. SLC41A1 is significantly overexpressed in nearly 55% of preeclamptic placentas. This may indicate a direct contribution of changed Mg homeostasis in the development of preeclampsia.